EFFECT OF LATERAL DEVELOPMENT OF PROSOPIS JULIFLORA DC. ROOTS ON AGRICULTURAL CROPS - Prajapati, M C; Verma, Balvir; Mittal, S P; Nambiar, K T N; Thippannavar, B S (Annals of Arid Zone, 2016)
Intensity and extent of lateral development of Prosopis juliflora hedge roots in agricultural field, their concentration in different depth zones and their effects on growth parameters of Sorghum vulgare crop were studied in three replications at Soil Conservation Research Station, Sreedharagada (Bellary) during 1670. Number of Prosopis juliflora roots in 0.6 m 2 area was maximum (1041). at distance Do (Base of the hedge), declining sharply and almost vanishing (7) at distance D7 (About seven time the hedge height). In cultivated field the major concentration of Prosoopis roots was 0-20 cm. depth evidently to favourable soil and moisture conditions owing to repeated tillage and fertiliser applications for raising crops. Number of Sorghum vulgare roots was minimum at distance D1 (about two time the hedge height) recording sharp rise upto distance D5 (fine time the hedge height) and then almost flattening thereafter. Growth and yield parameters of Sorghum crop were in conformity with it s number of roots. Sorghum plants bore no fruits at distance D1, yielded grains merely 42.0 kg/ha. (7%) at distance D2 and as much 612.0 kg/ha at distance D6. Maximum concentration of roots wa sin 20-40 cam depth. Shade due to Prosopis hedge had no adverse effect on crops in the tropical climate of Bellary. It is inferred that Prosopis juliflora roots are highly competing and permit no normal growth to other plant species in the root affected area